Risk, Benefit, and Cost Thresholds for Emergency Department Testing: A Cross‐sectional, Scenario‐based Study. (17th March 2017) - Meka, Arjun Prasad; Porath, Jonathan Douglas; Iyengar, Rahul; Morrow, Chelsea; Fagerlin, Angela; Meurer, William J.
Abstract: Background: While diagnostic testing is common in the emergency department, the value of some testing is questionable. The purpose of this study was to assess how varying levels of benefit, risk, and costs influenced an individual's desire to have diagnostic testing. Methods: A survey through Amazon Mechanical Turk presented hypothetical clinical situations: low‐risk chest pain and minor traumatic brain injury. Each scenario included three given variables (benefit, risk, and cost), that was independently randomly varied over four possible values (0.1, 1, 5, and 10% for benefit and risk and $0, $100, $500, and $1, 000 for the individual's personal cost for receiving the test). Benefit was defined as the probability of finding the target disease (traumatic intracranial hemorrhage or acute coronary syndrome). Results: One‐thousand unique respondents completed the survey. With an increased benefit from 0.1% to 10%, the percentage of respondents who accepted a diagnostic test went from 28.4% to 53.1%. (odds ratio [OR] = 3.42; 95% confidence interval [CI] = 2.57–4.54). As risk increased from 0.1% to 10%, this number decreased from 52.5% to 28.5%. (OR = 0.33; 95% CI = 0.25–0.44). Increasing cost from $0 to $1, 000 had the greatest change of those accepting the test from 61.1% to 21.4%, respectively (OR = 0.15; 95% CI = 0.11–0.2). Conclusions: The desire for testing was strongly sensitive to the benefits, risks, and costs. Many participants wanted a test when there was no added cost, regardless of benefit or risk levels, but far fewer elected to receive the test as cost increased incrementally. This suggests that out‐of‐pocket costs may deter patients from undergoing diagnostic testing with low potential benefit.